Recurrent Subretinal Hemorrhage in a Patient Taking a Turmeric Supplement: Case Report - Sherry Narang Kalla (Case Reports in Ophthalmology)
Introduction: This case report highlights the importance of knowing what nonprescription medications and supplements are being taken by patients in addition to their prescribed medications. Case Presentation: A 48-year-old myopic male presented with a 1-day history of hand motion vision. He was found to have an extensive vitreous hemorrhage with no view of the fundus. On follow-up 4 days later, he continued to have a significant vitreous hemorrhage and a B scan that showed a possible retinal tear. Upon having surgery 7 days later, he was found to have a temporal retinal detachment with subretinal fluid and hemorrhage extending to, but not involving, the macula. His postoperative course was complicated by persistent preretinal and subretinal hemorrhages along with recurrent retinal detachments requiring 2 additional surgeries. He was evaluated by his primary care physician and had a normal thrombotic work-up and all his dietary supplements, including turmeric, were discontinued. At post-op month 2, he continued to improve with resolving subretinal hemorrhage and an attached retina. Conclusion: This case report describes the extensive and recurrent subretinal hemorrhage that can develop in those patients taking medications or supplements with anticoagulant and/or antiplatelet properties. These antithrombotic agents are not only limited to prescription medications but can also include dietary supplements such as turmeric. It highlights the importance of knowing both the medications and dietary supplements a patient uses as this can affect the long-term outcome.